Operational cost comparison of alternative fuel vehicles for public transportation - Mercado, Jose Gabriel (Philippine Engineering Journal [eJournal])
This paper presents the operational cost analysis of different alternative fuel vehicles used for Public Utility Jeepneys (PUJs) in Metro Manila. Four models were generated using data from the UP-SM North Jeepney route. Model A used actual data gathered from the on-road tests conducted. Model B did not consider the downtime days to normalize the daily net income. Model C kept the costs not related to fuel and maintenance, jeepney fare, and data influence by the preference of the driver, constant. Model D assumed only jeepney type varied, without accounting for any preference mentioned in Model C. For all models, in terms of Fuel Cost (PhP) per Passenger-km, the Electric Jeepney is 35-49% more economical and has 1%-36% higher net income vs Diesel Jeepney. However, the LPG jeepney is less economical by 8%-18% vs Diesel Jeepney in Models A-C but more economical by 4% in Model D due to higher cost of Diesel fuel. In terms of Net Income (PhP) per Passenger-km, LPG Jeepney has 10% lower income vs Diesel Jeepney in Models A&B but has 5% higher income in Models C&D as considered days are the same, thereby minimizing differences in the number of passengers that affects both parameters.